Analisis Rantai Pasok dan Efisiensi Saluran Pemasaran Jamur Tiram di Desa Payakabung (Studi Kasus: Kelompok UMKM Jamur Tiram): Analisis Rantai Pasok dan Efisiensi Saluran Pemasaran Jamur Tiram di Desa Payakabung (Studi Kasus: Kelompok UMKM Jamur Tiram) - Rosana, Elly; Razuhri, Ghery (Departement of Socio-Economic Agricuture, Faculty of Agriculture, 2024)
One of the horticultural commodities that has the potential to be developed and has good prospects because it has a high economic value is oyster mushrooms. The Oyster Mushroom UMKM Group is one of the largest oyster mushroom producers in North Indralaya District, Ogan Ilir Regency. The objectives of this study are: (1) to describe the flow of oyster mushroom supply chain management products in the Oyster Mushroom UMKM Group in Payakabung Village, (2) to analyze the efficiency of oyster mushroom marketing channels in the Oyster Mushroom UMKM Group in Payakabung Village. The research was conducted in Payakabung Village, North Indralaya District, Ogan Ilir Regency in September - October 2024. The research method used in this study is the case study method. The sampling method used in this study is the purposive sampling and snowball sampling methods. Data collection was carried out through interview methods with the help of questionnaires and field observations. Data processing used descriptive methods and analysis of marketing channel efficiency. The results of the study indicate that the application of supply chain management to the flow of oyster mushroom products in the Oyster Mushroom UMKM Group is categorized as good from upstream to downstream, because each party establishes a well-integrated cooperation. Marketing channel I has a marketing efficiency level of 1.7%, while marketing channel II is 7.4%, the shorter the marketing flow, the more efficient the marketing channel.